Strong-field and time-resolved photoemission from plasmonic nanoparticles - Saydanzad, Erfan (Kansas State University, 2022)
In this dissertation, numerical models have been developed to investigate strong-field photoemission and attosecond streaking spectroscopy from plasmonic nanoparticles. Attosecond streaking spectroscopy and strong-field photoemission are powerful methods for investigating the electronic dynamics in gaseous atoms, that are currently being transferred to the investigation of collective electronic (plasmonic) effects in solids and nanostructures. First, a classical model is proposed to study plasmon excitations in metal nanoparticles using attosecond streaking spectroscopy. In this model, by sampling over classical photoelectron trajectories, we simulated streaked photoelectron energy spectra as a function of the time delay between ionizing isolated attosecond extreme ultraviolet pulses and assisting infrared or visible streaking laser pulses. Our theoretical model comprises a sequence of four steps: XUV excitation, electron transport in the nanoparticles, escape from the surface of the nanoparticles, and propagation to the photoelectron detector. Based on numerical applications to gold nanospheres, we investigated streaked photoemission spectra with regard to (i) the nanoparticle's dielectric response to the electric field of the streaking laser pulse, (ii) relative contributions of photoelectron release from different locations on and in the nanoparticle, (iii) contributions of photoemission from the Fermi level only versus emission from the entire occupied conduction band, and (iv) their fidelity in imaging the spatiotemporal distribution of the induced plasmonic field near the particle's surface. Second, based on this model, we suggest a method for reconstructing induced plasmonic fields with nm spatial and sub-fs temporal resolution from streaked photoemission spectra. Applying this imaging scheme to gold nanospheres, we demonstrated the accurate spatiotemporal reconstruction of the plasmonic near-field distribution in comparison with the directly calculated plasmonic field. Finally, strong-field photoemission from metal nanoparticles was modeled. The numerical model includes: (i) photoelectron emission on the nanoparticle surface by an intense infrared laser pulse, (ii) photoelectron propagation outside the nanosphere in the presence of the incident laser and induced plasmonic fields, and (iii) photoelectron rescattering and recombination to the nanoparticle. Based on simulated photoelectron-momentum distributions from gold nanospheres for two different intensities, and in comparison with velocity-map-image photoelectron spectra measured at the James R. Macdonald Laboratory, we scrutinize the effects of induced plasmonic fields, photoelectron correlations and electron-residual charge interactions, and photoelectron rescattering and recombination at the nanoparticle surface.
Keywords: Strong-field; Time-resolved photoemission; Plasmonic nanoparticles